Analysis of Internal Control and Fraud Prevention Efforts in Public Sector Accounting - Adelya Putri Kesuma; Fachruzzaman Fachruzzaman (UNIVED Press, 2024)
This study aims to analyze the effect of internal control on accounting fraud that occurs in the public sector. This research was conducted using a literature review by reviewing 10 previous articles both national and international articles. The keywords used in the iterator search include 'internal control', 'fraud', 'public sector accounting fraud'. The results of the review of 10 articles show that internal control is an effective effort in preventing accounting fraud in public sector organizations.